Quantum Pain Management Concept - Cengiz Mordeniz (Current Practice in Medical Science Vol. 10, 2022)
Pain hasn’t been objectively yet defined and evaluated until now. There are numerous components missing from the commonly recognised definition of pain, which results in exceptions to the rule. Something that cannot be accurately measured and properly managed cannot be scientifically well characterised. The traditional mechanistic approach to try to find a particular region in the brain or ascending pathway particular to pain may be the cause. After the failure of this strategy, new ideas like the pain matrix and the dynamic pain connectome were put forth. Because pain network is a multifractal and non-linear system that may be evaluated using quantum mechanics, and quantum information theory as well as complex and chaotic system analysis. As a result, a novel understanding of pain based on quantum mechanics is needed.